Numerical analysis of waste transport inside a building drainage network and sediments removal from ballast tanks using the Moving Particle Semi-Implicit. - Pereira, Lucas Soares (2021)
Fluid-solid interactions are complex dynamics phenomena with various applications in engineering, for example, fresh concrete flow, flow in a drainage system and sediment removal in ballast water exchange. Considering the complexity of those phenomena, the process cannot be precisely described through analytical solutions. The use of experimental models is an option, but due the high costs involved, this approach can be applied only for specific cases. Therefore, the computational approach has the advantages of flexibility and reduced costs. Traditionally, simulations of fluids are based on Eulerian description and meshes are necessary for the calculation. Over the years its disadvantages became clear when applying in phenomena with large deformation or moving boundary. Thereby, the meshfree methods were proposed toovercome these problems, an example is the Moving Particle Semi-implicit (MPS), it is based on a Lagragian description and discretization of the domain in particles. Originally, the MPS was developed for simulation of incompressible flows and was recently adopted in different applications. The advantage of the method is the capability to reproduce high non-linear phenomena with large deformation. In this study, the MPS is applied to investigate two processes involving fluid-solid interactions: waste transport inside a building drainage network, in which the solid is modeled as a rigid body, and sediments removal from ballast tanks, in which the sediments are modeled as denser fluids. The first study is a numerical investigation of the waste transport performance of a building drainage network under water conservation criteria, in which the reduced discharge volume results in an unsteady flow characterized by short duration and low energy. Due the intermittent flow in the initial sections of the drainage network, waste deposition in the horizontal drains that directly receive the effluents are of special concern. In the simulations, a simplified bathroom drainage model is adopted to investigate the influence of the pipe and discharge parameters. The hydrodynamics in the vicinity of a wye and its influence on the waste transport are also evaluated. Moreover, an investigation on the unphysical frictional loss inside a horizontal pipe due the wall boundary modeling is carried out. The results show that the pipe geometry modeling has significant influence on the numerical accuracy. In the second study, experiment and numerical simulations were carried out aiming to investigate the effectiveness of the flow-through method on the removal of the sediment accumulated in double bottom ballast tanks, that might be a habitat for invasive species and represent a threat for the biodiversity. The effects of the flow rate and the density of the sediments were also considered. In addition to this, two tank modifications aiming to improve the sediment removal were also evaluated: the presence of a flow deflector and injection of water from the bottom. The results show that the flow-through ballast water exchange method might not be effective to remove the sediments entrapped between the bottom stiffeners, and the proposed modifications, despite challenging implementation, improve the sediment removal.